Basic life support skills can be improved among certified basic life support instructors - Mathilde Stærk; Lauge Vammen; Camilla Fuchs Andersen; Kristian Krogh; Bo Løfgren (Resuscitation Plus, 2021)
Background: A correct visual skill demonstration is important when learning cardiopulmonary resuscitation (CPR) and the use of an automated external defibrillator (AED). Basic life support (BLS) instructors are expected to master and demonstrate CPR/AED skills correctly. The aim of this study was to evaluate certified BLS instructors’ competencies in demonstrating CPR and the use of an AED. Methods: Certified BLS instructors demonstrated CPR and the use of an AED on a resuscitation manikin. Skills were evaluated using data collected from the manikin and video recordings and compared to resuscitation guidelines. Further, instructors completed questionnaires on resuscitation guidelines and rating of their own CPR/AED skills. Results: Overall, we analyzed data from 125 instructors. Of all chest compressions, only 22% were within guideline recommendations regarding depth. Instructors performed chest compressions with excessive depth (mean depth 64 mm (7.3)) and a mean rate of 115 min−1 (10.8). Only 25% of instructors placed the left AED electrode correctly (median distance 7.6 cm (5.0;10.5)), while the right AED electrode usually was placed correctly (median distance 2.9 cm (1.5;4.0), 85% placed correctly). Nearly half of the instructors failed to state correct answers regarding how to diagnose a cardiac arrest and where to place the AED electrodes. Despite their performance, instructors rated their BLS skills as good. Conclusion: Certified BLS instructors’ have poor CPR/AED skills and several important knowledge gaps on CPR/AED guidelines in contrast to instructors’ self-reported skills. This highlights a need for improving BLS instructor education, including continuous faculty development to ensure optimal learning conditions for BLS course participants.